2012
DOI: 10.1371/journal.pgen.1002492
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function of the Cik1/Kar3 Motor Complex Results in Chromosomes with Syntelic Attachment That Are Sensed by the Tension Checkpoint

Abstract: The attachment of sister kinetochores by microtubules emanating from opposite spindle poles establishes chromosome bipolar attachment, which generates tension on chromosomes and is essential for sister-chromatid segregation. Syntelic attachment occurs when both sister kinetochores are attached by microtubules from the same spindle pole and this attachment is unable to generate tension on chromosomes, but a reliable method to induce syntelic attachments is not available in budding yeast. The spindle checkpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 59 publications
(83 reference statements)
3
40
0
Order By: Relevance
“…The cosegregation of CEN4-GFP in bub1-DK cells indicates checkpoint arrest failure. Our previous study showed that overexpression of CIK1-CC in sgo1D cells caused .30% CEN4-GFP missegregation using the same analysis (Jin et al 2012), which is higher than that of bub1-DK cells. One explanation is that Sgo1 is still functional enough in bub1-DK cells to prevent SAC silencing, but less efficient due to the failure of centromere localization.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The cosegregation of CEN4-GFP in bub1-DK cells indicates checkpoint arrest failure. Our previous study showed that overexpression of CIK1-CC in sgo1D cells caused .30% CEN4-GFP missegregation using the same analysis (Jin et al 2012), which is higher than that of bub1-DK cells. One explanation is that Sgo1 is still functional enough in bub1-DK cells to prevent SAC silencing, but less efficient due to the failure of centromere localization.…”
Section: Resultsmentioning
confidence: 87%
“…We showed that Ipl1 kinase and Sgo1 are required to prevent SAC silencing in response to syntelic attachment induced by CIK1-CC overexpression (Jin et al 2012;Jin and Wang 2013). Because the centromere localization of Sgo1 depends on H2A phosphorylation by Bub1 kinase (Fernius and Hardwick 2007;Kawashima et al 2010;Nerusheva et al 2014), Bub1 kinase activity might be required to prevent SAC silencing in response to syntelic attachment, although this kinase activity is dispensable for SAC activation (Fernius and Hardwick 2007).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations